Social Inequality and Food Security in Indonesia: The Role of Education - Nuresa Safitri; Istiqomah Istiqomah (Institut Pertanian Bogor, 2026)
This study evaluates the impact of social inequality, measured by gini index and poverty rate, on food security across Indonesian provinces during the 2019–2023 period, incorporating the mean years of schooling as a moderating variable. Utilizing panel data from 34 provinces and a fixed effects model, the findings reveal that poverty has a significant negative effect on food security, while the gini index representing income inequality shows no effect. However, when moderated by education, the gini index becomes significant, highlighting the role of education in amplifying the effects of social inequality. Provinces with higher education levels display greater sensitivity to poverty and inequality because of increased expectations for food quality and living standards. Education functions as a direct determinant and as a social mechanism that enhances nutritional literacy, awareness of equitable food distribution, and community adaptive capacity during food crises. These results underscore the need for effective food security policies that integrate human capital development strategies, particularly in education. Practical implications include the promotion of agricultural education, food literacy training, and community empowerment programs in vulnerable regions. This study recommends a multidimensional approach to food security policies that extends beyond production and distribution to emphasize social equity, poverty reduction, and educational strengthening. Keywords: food security, gini index, mean years of schooling, poverty rate, social inequality